Positive Reinforcement Strategy to Improve Juz Amma Memorization - Helmawati; Hasan; Dede Rosandi; Miftahul Huda (Indonesian Journal of Islamic Religious Education, 2025)
The habit of memorizing Juz Amma among elementary school students is both commendable and beneficial, particularly in supporting daily prayer practices. To enhance this memorization, effective strategies are required one of which is the use of positive reinforcement. This study aims to explore how positive reinforcement strategies can effectively improve students’ memorization of Juz Amma. A descriptive qualitative method was employed, with data collected through observation, interviews, and document analysis. Data were analyzed using content analysis supported by cross-checking and triangulation techniques. The findings reveal that the positive reinforcement strategy involves a structured procedure: identifying (planning) the target behaviors, selecting appropriate types of positive reinforcement, maintaining consistency in implementation, and conducting evaluation during the memorization process. The impact of this strategy is reflected in improved cognitive abilities, attitudes, and skills of the students throughout the Juz Amma memorization process. The study demonstrates that when applied consistently and appropriately, positive reinforcement strategies significantly contribute to the development of students’ cognitive, affective, and psychomotor domains in the context of memorizing Juz Amma.